2004
DOI: 10.1016/j.vetimm.2004.09.006
|View full text |Cite
|
Sign up to set email alerts
|

The combination of PRRS virus and bacterial endotoxin as a model for multifactorial respiratory disease in pigs

Abstract: This paper reviews in vivo studies on the interaction between porcine reproductive and respiratory syndrome virus (PRRSV) and LPS performed in the authors' laboratory. The main aim was to develop a reproducible model to study the pathogenesis of PRRSV-induced multifactorial respiratory disease. The central hypothesis was that respiratory disease results from an overproduction of proinflammatory cytokines in the lungs. In a first series of studies, PRRSV was shown to be a poor inducer of TNF-alpha and IFN-alpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 77 publications
3
45
1
1
Order By: Relevance
“…LPS has been used in swine models of infection with PRRSV (61,60) and porcine respiratory coronavirus (PRCV) (62). In all these works, the aim was to repro-FERNANDES ET AL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LPS has been used in swine models of infection with PRRSV (61,60) and porcine respiratory coronavirus (PRCV) (62). In all these works, the aim was to repro-FERNANDES ET AL.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that LPSs of Escherichia coli and Salmonella spp. have stronger endotoxic activity than those of other bacteria (60). Therefore, based on this fact and due to the fact that one of the best in vitro results for the Stoon-1010 isolate (the same phylogenetic group as the Burgos isolate) was with the LPS from Salmonella enterica serotype typhimurium, this LPS was chosen for the in vivo study.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, vaccination of piglets is more controversial. Firstly, because respiratory disease caused by PRRSV, particularly by genotype 1 isolates, is not always overt (Martínez-Lobo et al, 2011) and depends on the interaction with other pathogens (Van Gucht et al, 2004). Therefore, the beneficial effect of vaccination is more difficult to evaluate.…”
Section: Introductionmentioning
confidence: 99%
“…PRRSV can cause severe reproductive failure in sows, characterized by late term abortion, early farrowing, stillbirth and the birth of weak piglets, and is associated with the porcine respiratory disease complex in combination with secondary infections [3,4,[26][27][28]30]. The virus is present in a majority of swine producing countries around the world and gives rise to enormous economic losses in the swine industry [17].…”
Section: Introductionmentioning
confidence: 99%